Optimizing the LNG-Based Ambon Island Electricity System: An Energy Policy Analysis Using the Dynamic Economic Dispatch Approach - Sulaksono, Nugroho Budi; Wibowo, Rony Seto (Indonesian Journal of Social Science Research, 2026)
The electric power system on isolated islands like Ambon Island still relies on oil-fired power plants, which results in high operating costs, low efficiency, and significant carbon emissions. This study evaluates the utilization of Liquefied Natural Gas (LNG) through regasification facilities as energy gas storage to support gas engine power plants, with the aim of optimizing power plant operations and reducing electricity system operating costs. The analysis was conducted using a Dynamic Economic Dispatch (DED) approach based on Mixed Integer Linear Programming (MILP), considering the technical limitations of the power plant, ramp rate, power balance, and LNG regasification capacity within a 24-hour operating horizon. Simulation results show that converting fuel oil to LNG at the PLTMG and BMPP units reduces daily operating costs by Rp306 million, equivalent to a savings of 12.67%, and shifts the role of gas generators as baseload and reduces dependence on high-cost diesel generators. Sensitivity analysis shows that investment in regasification facilities remains feasible as long as daily fixed costs are below the break-even point of Rp806 million per day. These findings support the achievement of SDGs 7 (Affordable and Clean Energy) and SDGs 13 (Climate Action) by increasing energy efficiency, reducing emissions, and strengthening energy security in the archipelago.